Analysis of Relationship between Effectiveness of Internal Control System and Audit Opinions on Local Government Financial Statements - Indra Kesuma; Irwan Taufiq Ritonga (The Indonesian Journal of Accounting Research, 2020)
This study aims to analyse and to describe relationship between effectiveness of internal control system (ICS) and audit opinion of the Audit Board (the AB) of the Republic of Indonesia on Local Government Financial Statements (LGFS). In addition, this study also aims to explain the consideration of ICS effectiveness in the process of formulating audit opinion. This study uses an explanatory sequential mixed method. This study uses a different approach compared to previous research by considering materiality factors in assessing effectiveness of ICS. Sample of this study is fifty four local government in Indonesia. Analytical tools used include content analysis, correlation analysis, mean difference tests, and textual data analysis. Content analysis is performed on fifty four ICS Audit Reports year 2017, correlation analysis utilizes Somer’s d and Kendall’s tau c, and mean difference test analysis uses Kruskal Wallis. Meanwhile, textual data analysis is carried out on the results of interviews with nine auditors from three AB representative offices in Java. Results of this study show that effectiveness of ICS has a strong and positive relationship with audit opinion on LGFS. In addition, average score of ICS effectiveness is different for each group of LGFS audit opinion. This fact shows that the AB has considered ICS effectiveness in formulating audit opinions. Results of interview show that pattern of relationship between effectiveness of ICS and audit opinion is indirect. The AB considers effectiveness of ICS in the phase of determining audit planning materiality rate and in the phase of analyzing impact of ICS findings on the fairness of LGFS. Implication of this results is that the government should revise audit regulations by removing ICS effectiveness as one of factors that must be considered in the formulation of audit opinion because ICS effectiveness and audit opinion are not directly related.